Nilai Didaktis Cerita Rakyat Calon Arang dan Implementasinya dalam Dunia Pendidikan - Dewa Ayu Kadek Claria; Made Subur; I Ketut Subagia (Departement of Mathematics Education, 2023)
Folklore which is adapted into the form of performances are currently more interesting than folklore in written form. In perfomances, many educational messages are often inserted and highlighted based on the moral values of the character which can elevate the value of folklore itself. Research on the values contained in stories allows for the discovery of system that underlies the information of text. The result can be used as a reference in developing other folklore especially the development also can be used to develop the learner’s character. This research is a qualitative descriptive study. The data taken from text Calon Arang by I Gede Semadi Astra and I Wayan Bawa which is widely adapted into barong dance performances that are offered as a tourist attraction in Bali and also implemented in teaching literature at college.